Africa in global development - Kouakou, Alban (Revista Española de Desarrollo y Cooperación, 2023)
With mundialization failing in the West, African development faces with a model crisis.If North-South cooperation appears harmful, Asian developmental state model seduces.But the idea of the new Marshall Plan for Africa raises new doubts and concerns.This article argues that there are actually some good expectations about African development that should be consolidated reinventing the regional government.